Place of Devotion: Siting and Experiencing Divinity in Bengal-Vaishnavism - Sarbadhikary, Sukanya (South Asia Across the Disciplines, 2015)
Hindu devotional traditions have long been recognized for their sacred geographies as well as the sensuous aspects of their devotees' experiences. Largely overlooked, however, are the subtle links between these religious expressions. Based on intensive fieldwork conducted among worshippers in Bengal's Navadvip‑Mayapur sacred complex, this book discusses the diverse and contrasting ways in which Bengal‑Vaishnava devotees experience sacred geography and divinity. Sukanya Sarbadhikary documents an extensive range of practices, which draw on the interactions of mind, body, and viscera. She shows how perspectives on religion, embodiment, affect, and space are enriched when sacred spatialities of internal and external forms are studied at once.